The Hidden Curriculum in Islamic Education: Developing Critical Thinking and Moderate Attitudes among Students - Nur Fuad, Ai Fatimah; Rafa Basyirah; Ihsana El Khuluqo (Program Studi Pendidikan Agama Islam (PAI), 2024)
The hidden curriculum serves as a supplementary component to the formal curriculum, emphasizing the cultivation of students' character. One crucial aspect of character development for students is the ability to exhibit critical thinking and moderation. This research aims to make a hidden curriculum as a tool and effort to build students' critical thinking and moderate attitudes. The method of this study is qualitative. Data is collected through observation, interviews, and written documentation and literature. The sources of data and information are obtained from 9 informants which are the school principal, deputy principal for the curriculum section, Pancasila, Islamic and Christian Education teachers, class teachers, and 3 students at SMAN 60 Jakarta. The scope of this research only covers the development, implementation, and obstacles of the hidden curriculum increase students' critical and moderate attitudes. The implications of this research are the awareness of schools regarding the importance of paying attention to the hidden curriculum in schools and addressing existing constraints. Additionally, further research is needed on the role of government policies in hidden synchronization.